Different Types of Diatom-Derived Extracellular Polymeric Substances Drive Changes in Heterotrophic Bacterial Communities from Intertidal Sediments - Bohórquez, Julio; McGenity, Terry J.; Papaspyrou, Sokratis; García-Robledo, Emilio; Corzo, Alfonso; Underwood, Graham J. C. (Frontiers in Microbiology, 2017)
Intertidal areas support extensive diatom-rich biofilms. Such microphytobenthic (MPB) diatoms exude large quantities of extracellular polymeric substances (EPS) comprising polysaccharides, glycoproteins and other biopolymers, which represent a substantial carbon pool. However, degradation rates of different EPS components, and how they shape heterotrophic communities in sediments, are not well understood. An aerobic mudflat-sediment slurry experiment was performed in the dark with two different EPS carbon sources from a diatom-dominated biofilm: colloidal EPS and the more complex hot-bicarbonate-extracted EPS. Degradation rate constants determined over 9 days for three sediment fractions (dissolved organic carbon (DOC), total carbohydrates (TCHO) and colloidal EPS (cEPS)) were generally higher in the colloidal-EPS slurries (0.105–0.123 d-1) compared with the hot-bicarbonate-extracted-EPS slurries (0.060–0.096 d-1). Addition of hot-bicarbonate-EPS resulted in large increases in dissolved nitrogen and phosphorous by the end of the experiment, indicating that the more complex EPS is an important source of regenerated inorganic nutrients. Microbial biomass increased ~4 to 6-fold over 9 days, and pyrosequencing of bacterial 16S rRNA genes revealed that the addition of both types of EPS greatly altered the bacterial community composition (from 0 to 9 days) compared to a control with no added EPS. Bacteroidetes (especially Tenacibaculum) increased ~3-fold (relative abundance) in the hot-bicarbonate-extracted-EPS treatment, whereas Verrucomicrobia were enriched significantly (~2.5-fold) only in the colloidal-EPS treatment. These differential effects of EPS fractions on carbon-loss rates, nutrient regeneration and microbial community assembly improve our understanding of coastal-sediment carbon cycling and demonstrate the importance of diverse microbiota in processing this abundant pool of organic carbon.